Formal education and nurses’ attitudes towards alcohol and alcoholism in a Brazilian sample - Pillon, Sandra Cristina; Laranjeira, Ronaldo Ramos (São Paulo Medical Journal, 2005)
CONTEXT AND OBJECTIVE: Nurses are one of the largest groups of healthcare professionals sharing in patient care responsibilities, including caring for those who use and abuse psychoac- tive substances. The objective was to evaluate the theoretical-practical knowledge acquired by nurses in undergraduate and postgraduate studies and their perceptions about alcohol users. DESIGN AND SETTING: Quantitative, descriptive survey at Universidade Federal de São Paulo — Escola Paulista de Medicina and Hospital São Paulo. METHODS: The sample included nurses, students and nursing teachers. The survey included ques- tions about sociodemographic characteristics; a nurses’ attitudes and beliefs scale; and a ques- tionnaire to identify formal nursing education on the use of alcohol and its consequences. RESULTS: 59.7% out of 319 volunteers were nurses, 22.7% were nursing teachers and 17.6% were nursing students. 70% of the participants had received little or no information on physical, family and social problems related to alcohol use; 87% had received little or no information on high risk related to specific segments of the population; 95% had received little or no information on nursing procedures for alcohol-abuse patients. CONCLUSION: Formal education regarding the use of alcohol and its consequences is limited, especially with regard to offering adequate care and management for patients who have problems with or are addicted to alcohol.